Immunological and Hematological Responses of Labeo rohita under Starvation - Kanwal, Naila Noreen; Abdullah, Sajid; Hayat, Sikandar; Abbas, Sidra; Saqlain, Muhammad; Wasif, Zunaira; Wakeel, Javeria; Luqman, Muhammad (Journal of Agriculture and Biology, 2025)
In aquaculture, fish health and food are of great concern but improper management of aquaculture leads to fasting stress and disturbed fish health. Food shortage may alter the immune system of fish affecting overall health and wellbeing of fish. The current study was designed to check the possible alterations that may occur in the immunological parameters of Labeorohita. The experiment was conducted for 30 days fisheries research farm, department of Zoology, wildlife and fisheries, University of Agriculture Faisalabad. Labeorohita fingerlings were collected from fish seed hatchery. The fish were procured, acclimatized and then distributed into two groups control and starved. The first group, referred as control group, fed twice a day. The second starved group, was detained in a hungry state for 28 days. Blood samples were drawn from the caudal vein of fish at the intervals of 7, 14, 21 and 28 days to examine the immunological and hematological parameters. The results showed that hematological and immunological parameters of starved group were reduced as compared to control group. The Hb, RBC, HCT, MCH, MCV, MCHC, white blood cells, monocytes, lymphocytes, eosinophils, neutrophils, granulocytes, were significantly reduced in starved group as compared to control group. The results of this study suggest fasting for period of 30 days cause significant reduction in the immunological and hematological parameters of fish.
Keywords: Labeorohita; Immunological; Hematological; Starvation